1931
DOI: 10.1002/hlca.19310140105
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen über die Membran der Sporen und Pollen III. 2. Picea orientalis, Pinus silvestris L., Corylus Avellana L

Abstract: V e r s e i f u n g d e r tlrei A c e t y l p r o d u k t e uncl B e s t i m m u n g ctes Die drei Acetylprodukte wurden mit je 50 em3 0.1-n. alkoholischer Kalilauge in ejnem Schliffkolben 7 Stunden gekocht ; hierauf wurde die unverbrauchte Lauge rnit 0,l-n. Salzshre, mit Phenolphtalein als Inclikator, zuruektitriert. Ds das Sporonin kein Alkali bindet, konnte die Titration direkt in den zur T'erseifung benutzten Kolben vorgenommen werden. a) 0,2562 g Subst. (0,2537 g aschefrei) verbrauchten 1T,O cm3 0,l-n. KO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1931
1931
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…The cell walls of the Chlorophyta are composed of sporopollenin (Zetsche and Vicari 1931), the same Palynology 157 material as that of pollen grains and fern spores, making them similarly resistant to destruction during fossilisation and chemical laboratory processing.…”
Section: Chlorophyta (Green Algae)mentioning
confidence: 99%
“…The cell walls of the Chlorophyta are composed of sporopollenin (Zetsche and Vicari 1931), the same Palynology 157 material as that of pollen grains and fern spores, making them similarly resistant to destruction during fossilisation and chemical laboratory processing.…”
Section: Chlorophyta (Green Algae)mentioning
confidence: 99%
“…Bioparticles, however, are also the pollen grains of seed plants but have found so far little attention from this point of view. Chemical analysis showed a molecular formula of (C 10 H 16 O 3 ) x , where the H and O content has a certain variability [4]. Pollen is known by many people just as annoying allergy-causing material.…”
Section: Introductionmentioning
confidence: 99%
“…The biosynthesis, chemical composition and ultrastructure of sporopollenin are not resolved completely up to now. Chemical analysis showed a molecular formula of (C 10 H 16 O 3 ) x , where the H and O content has a certain variability [4]. Recent studies showed that the sporopollenin is a heteropolymer consisting of aliphatic and aromatic polymer-linked compounds with carboxyl, carbonyl and ether functions [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…He also demonstrated that apertures are predetermined in most angiosperm pollen while others are inaperturate. Zetzsche first coined the term "sporopollenin" to describe the resistant chemical substance present in the outer wall of both pollen grains and spores (Zetzsche and Huggler 1928;Zetzsche and Vicari 1931;). Campbell reported pollen of seagrasses (Naias and Zannichellia) to be thin walled, without exospore (exine), and two-celled.…”
Section: The History Of Palynologymentioning
confidence: 99%